Case review: hearing and balance loss in Creutzfeldt-Jakob disease - Stewart, Christopher; Hamdan, Diana; Hansen, Blake; Ballard, Karson; Gotti, Brandy; Otto, Alex; Sukpraprut-Braaten, Suporn; McIntire, Kent (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Creutzfeldt-Jakob disease (CJD) is a rare transmissible neurodegenerative disease caused by misfolded prion proteins leading to rapid mental deterioration and death. Misfolded prion proteins form insoluble aggregates that cause irreversible neurological damage. While typically presenting with symptoms such as cognitive decline and behavioral changes, atypical presentations of CJD include symptoms such as sensorineural hearing loss or balance loss. The goal of this study is to systematically characterize atypical presentations of CJD with hearing and balance loss following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The PubMed database was utilized to analyze all case reports from the years 1990 to 2024 using the keywords “Creutzfeldt-Jakob disease”, “hearing loss”, and “balance”. A total of 16 cases were retrieved, and 11 were included in the study. Among cases retrieved, we identified eight patients with hearing loss and three with balance loss. Of hearing loss patients, four (50%) were male and four (50%) were female. The average age was 63.75 years (SD=11.17 years). The most common symptoms that accompanied hearing loss were analyzed (N, %), and include gait disturbances (8, 100%), myoclonus (6, 75%), cognitive impairment (4, 50%), akinetic mutism (4, 50%), and vision disturbances (4, 50%). The tests utilized to diagnose CJD in patients with hearing loss included MRI (5, 63%), EEG (5, 63%), and 14-3-3 protein (4, 50%). These findings highlight the importance of recognizing hearing and balance loss as potential early symptoms of CJD to aid in earlier diagnosis and a better understanding of disease progression.